Provincializing memory studies: The insistence of the 'here-now'. (October 2020) - Collins, Felicity; Healy, Chris; Radstone, Susannah
This essay responds to Astrid Erll's question about what it might mean to do memory studies in different parts of the world. We offer a response from the perspective of three researchers based in Australia. Focused on a season-opening gala performance, a photographic series, a site-specific protest, and a film that takes a choir from Central Australia to Germany, the essay tracks the emergence, in culture, of something we term the 'here-now'. The essay argues that this 'here-now' belongs neither to historical temporality's linear time-line, nor to the cosmology of an unsullied Indigenous culture – and cannot easily be addressed in the language of memory studies. Taking our lead from four case studies, we try to find words for what it is that the 'here-now' makes present, as it emerges in the artworks and events we discuss. We find that the 'here-now's' ordering of place/time insistently evokes a yet-to-be realized Australia, while prompting recognition of the hard truths that still stand in its way.